Analysis of Street Vendors Income Disparity in Tavip Market, Binjai District, North Sumatra City - Novianta Barus, Heni; Elfi Barus, Elida (Journal of Management Sains (JMS), 2025)
This study aims to determine the income disparity of street vendors in Tavip Market, Binjai District, North Sumatra City. This research method uses descriptive quantitative using primary data obtained from surveys, interviews, questionnaires, and documentation from street vendor respondents. The data analysis tool in this study is the Gini Ratio. The results showed that the income distribution of the first class of street vendors was 20%, the second was 25%, the third was 20%, the fourth was 15%, and the fifth was 20% with a total income percent of 100%. The cumulative income in class also shows that the first class is 20%, the second is 45%, the third is 65%, the fourth is 80%, and the fifth is 100%. The value of the Gini Ratio coefficient obtained is 0,35%, indicating that the level of income inequality of street vendors is in the low-income category. This has implications for the tight competition in buying and selling goods, which requires traders to be more creative and innovative in transactions in order to attract more customers.